TES DIAGNOSTIK SEBAGAI INSTRUMEN EVALUASI AWAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Achmad Rasyid Ridha; Fatimah Az Zahrah; Fadhilah Wardatul Muslimah (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
A diagnostic test is a form of evaluation conducted before the start of learning to identify students' initial abilities, strengths, weaknesses, and misconceptions. In the context of Islamic Religious Education (PAI), this test plays a crucial role in determining students' readiness to learn, including cognitive, affective, and psychomotor aspects. With diagnostic test results, teachers can design more targeted learning, provide remedial classes, and tailor enrichment programs to meet students' needs. This paper discusses the definition of diagnostic tests, the purpose of their application in Islamic Religious Education (PAI) learning, the types of diagnostic tests, both cognitive and non-cognitive, and the steps involved in developing them. The discussion demonstrates that diagnostic tests are not only an evaluation tool but also an instrument for improving the learning process to make it more effective, adaptive, and oriented to student needs.